Нүүдэлчдийн нийгмийн харилцааны түүх - Батсайхан, Загд (Historia Mongolarum, 2003)
In this article the author has dealt with the issue of social history of nomads on the example of Xiongnu. In the 300 BC at the Central Asian region were established this nomadic state, which was characterized by high level of pasture farming, culture, ideology, social relations and the organization, and the structure of the state. The determinative of nomadic power was the first xiongnu state, our progenitor.